2013
DOI: 10.1146/annurev-physiol-030212-183705
|View full text |Cite
|
Sign up to set email alerts
|

Claudins and the Kidney

Abstract: Claudins are tight junction membrane proteins that regulate paracellular permeability of renal epithelia to small ions, solutes and water. Claudins interact within the cell membrane and between neighboring cells to form tight junction strands and constitute both the paracellular barrier and pore. The first extracellular domain of claudins is thought to be the pore-lining domain and contains the determinants of charge selectivity. Multiple claudins are expressed in different nephron segments and this likely det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
106
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
2

Relationship

4
6

Authors

Journals

citations
Cited by 136 publications
(115 citation statements)
references
References 116 publications
(159 reference statements)
1
106
0
Order By: Relevance
“…24 The paracellular Ca ++ transport in the TALH of the kidney involves the functional interplay of three important claudin genes: claudin-14, -16, and -19 (all of which are associated with human kidney diseases of hypercalciuria, nephrolithiasis, and bone mineral loss). 25 In a previous report, we showed that claudin-14 inhibits claudin-16 permeability and integrates into the claudin-16 and -19 channel complex in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…24 The paracellular Ca ++ transport in the TALH of the kidney involves the functional interplay of three important claudin genes: claudin-14, -16, and -19 (all of which are associated with human kidney diseases of hypercalciuria, nephrolithiasis, and bone mineral loss). 25 In a previous report, we showed that claudin-14 inhibits claudin-16 permeability and integrates into the claudin-16 and -19 channel complex in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…The predominant Ca ++ reabsorption sites are in the PT, the TALH, and the DCT. 11,12 Although the PT and TALH use the paracellular pathway to handle Ca ++ , 11 the DCT relies on a coordinated transcellular Ca ++ transport pathway based on the apically localized transient receptor potential channel V member 5 (TRPV5) and the basolaterally localized Na + /Ca ++ exchanger 1 (NCX1). 12 Because HDAC is a global regulator of gene expression, its renal effects could stem from different tubular segments.…”
mentioning
confidence: 99%
“…The claudins are a 28-member family of tetraspan proteins that range in molecular mass from 20 to 28 kDa and form a class of ion channels oriented perpendicular to the membrane plane and connecting two extracellular compartments, known as the paracellular channel (13). Claudins associate by cis interactions within the plasma membrane of the same cell followed by trans interactions between neighboring cells to assemble them in the TJ.…”
mentioning
confidence: 99%